Exposure to Bile Leads to the Emergence of Adaptive Signaling Variants in the Opportunistic Pathogen Pseudomonas aeruginosa - Flynn, Stephanie; Reen, F. Jerry; O’Gara, Fergal (Frontiers in Microbiology, 2019)
The chronic colonisation of the respiratory tract by the opportunistic pathogen Pseudomonas aeruginosa is the primary cause of morbidity and mortality in Cystic Fibrosis (CF) patients. P. aeruginosa has been shown to undergo extensive genomic adaptation facilitating its persistence within the CF lung allowing it to evade the host immune response and outcompete co-colonising residents of the lung microbiota. However, whilst several studies have described the various mutations that frequently arise in clinical isolates of P. aeruginosa, the environmental factors governing the emergence of these genetic variants is less well characterised. Gastro-oesophageal reflux has recently emerged as a major co-morbidity in CF and is often associated with the presence of bile acids in the lungs most likely by (micro) aspiration. In order to investigate whether bile may select for genetic variants, P. aeruginosa was experimentally evolved in Artificial Sputum Medium, a synthetic media resembling environmental conditions found within the CF lung. Pigmented derivatives of P. aeruginosa emerged exclusively in the presence of bile. Genome sequencing analysis identified single nucleotide polymorphisms (SNPs) in quorum sensing (lasR) and both the pyocyanin (phzS) and pyomelanin (hmgA) biosynthetic pathways. Phenotypic analysis revealed an altered bile response when compared to the ancestral P. aeruginosa progenitor strain. While the recovered pigmented derivatives retained the bile mediated suppression of swarming motility and enhanced antibiotic tolerance, the biofilm and redox responses to bile were abolished in the adapted mutants. Though loss of Pseudomonas Quinolone Signal (PQS) production in the pigmented isolates was not linked to the altered biofilm response, the loss of redox repression could be explained by defective Alkyl-Quinolone (AQ) production in the presence of bile. Collectively, these findings suggest that the adaptive variants of P. aeruginosa that arise following long term bile exposure enables the emergence of ecologically competitive sub-populations. Altered pigmentation and AQ signaling may contribute to an enhancement in fitness facilitating population survival within a bile positive environment.